Constructing Methods for Irreducible Polynomials - Alizadeh, Mahmood (Mathematical Problems of Computer Science, 2021)
In this paper we study the irreducibility of some composite polynomials, constructed with a polynomial composition method over finite fields. Furthermore, a recurrent method for constructing families of irreducible polynomials of higher degree from given irreducible polynomials over finite fields is given.